Basic characteristics of emigration of Croatian population with the focus on emigration in the past fifteen years - Mesarić Žabčić, Rebeka (Two Homelands, 2007)
The article analyses emigration of Croatian population in the last fifteen years. It is methodologically based on the analysis of data provided in the reports of the Central Bureau of Statistics, i.e. in the official reports on international migration of population of Croatia, due to absence of valid population census. Until 19991 there were so-called inter-republic migrations occurring between Croatia and Slovenia. After 1991, Croatia and Slovenia became independent and internationally recognised states. Therefore, Croatian emigration to Slovenia became international in its character, although it was still a continuation of the once inter-republic migration flows. On the basis of the analysis of situation during the past fifteen years it is concluded, that 147.252 Croatian citizens, aged from 30 to 45, emigrated from the Republic of Croatia. Therefore, in the last fifteen years Croatia lost a demographic potential as high as the number of residents of the town Rijeka. Because methodologies of statistics are not harmonised, the monitoring of emigration is difficult. This is also so due to inability to determine a precise number of Croatian emigrants on the basis of reports by the Ministry of Interior, because in the Republic of Croatia an emigrant is not required to report the change of address. Therefore, the results cannot be considered as entirely correct and valid.